Integrasi Nilai Budaya Lokal dalam Pendidikan Islam di Thailand Selatan - Dena Yulianto; Nafisa Dhabitah; Saskia Dwi Agnesia (INDO PUBLISHING, 2026)
The integration of local cultural values in Islamic education is an important effort to maintain the religious and cultural identity of Muslim communities in Southern Thailand. Regions such as Pattani, Yala, and Narathiwat have strong Malay traditions that persist despite the dominance of Thai national culture. This study aims to examine how local cultural values are integrated into Islamic education and their role in shaping students' character. The method used is library research with a qualitative descriptive approach. The results show that the integration of local values, such as the use of the Malay language, religious traditions, and social values, strengthens religious understanding while preserving cultural identity. However, this integration also faces challenges such as government policies, globalization, and social conflict. Therefore, appropriate strategies are needed to ensure Islamic education remains relevant and contextual.